ETHNOPHARMACOLOGICAL SURVEY OF MEDICINAL HERBS USED BY RURAL AND TRIBAL COMMUNITY IN BETUL DISTRICT OF MADHYA PRADESH, INDIA - Patil, U. K.; Bhargava, C. S.; Yadav, S. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The study of local knowledge about traditional herbal medicine is becoming increasingly important in defining strategies and actions for conservation of medicinal plants. This study therefore considered it worthwhile to collect information from local rural and tribal population living in Betul district of Madhya Pradesh (India) concerning the use of medicinal plants; identify the most important species used; determine the relative importance of the species surveyed and calculate the informant consensus factor (ICF) in relation to medicinal plant use. Data collection relied predominantly on qualitative tools to record the interviewee’s personal information and topics related to the medicinal use of specific plants. The present study revealed that 119 plant species grown in the study region are in use by rural and tribal community in traditional medicine for the treatment of various diseases. Most of the locals interviewed dealt with well-known safe medicinal plants, such as Allium sativum, Acacia arabica, Emblica offficinalis, Momordica charantia and Ocimum sanctum with use values of 0.62, 0.54, 0.52, 0.51 and 0.50 respectively. Dental, inflammation-pain and female problems scored the highest ICF of 0.85, 0.78 and 0.77 respectively. The literature from different Indian traditional systems of medicine evidenced some concordance with the solicited plant uses mentioned by the rural and tribal informants. Acknowledgements: CDACR, Bhopal for financial assistance.